Scientists in Organizations – Productive Climates for Research and Development - Marion, Gérald (Relations industrielles / Industrial Relations, 1968)
This article reviews "Scientists in Organizations – Productive Climates for Research and Development" by Donald C. Pelz and Frank M. Andrews.
Keywords: SnR_publicationTitle_Relations industrielles_Relations industrielles / Industrial Relations_2025-09-22T15:31:55.974Z